Tantangan dan Peluang Sinergi Pendanaan Pemerintah Daerah di Era Ketidakpastian Global Menuju Indonesia Emas 2045 - Suwanda, Dadang; Suwanda, Siti N. (Ekonomis: Journal of Economics and Business, 2025)
Regional fiscal revenue and management face significant challenges amidst global uncertainty, marked by the post-pandemic health crisis, extreme climate change, and technological disruption that are changing local economic dynamics, with the realization of Regional Transfers only reaching 62.1% of the target of Rp. 919.87 trillion and flood losses of Rp. 2.5 trillion in West Java. This study aims to analyze the synergy of central-regional funding to support local government adaptation towards the vision of Golden Indonesia 2045 through sustainable and inclusive development. A descriptive qualitative approach was applied through document studies (RPJPN 2025–2045, APBN 2025, regional APBD), in-depth interviews with 15 officials, and Focus Group Discussions (FGD) in West Java and North Sulawesi. The study results indicate three main challenges: fiscal policy disharmony, limited fiscal capacity that hinders regional autonomy, and vulnerability to external shocks such as global economic fluctuations; as well as innovation opportunities through the Regional Endowment Fund with an allocation of IDR 5 billion in Bandung Regency, KPBU in Bitung that increased fisheries exports by 15%, and e-budgeting that reduced budget leakage by 5%. The study recommends strengthening digital-based fiscal coordination, increasing regional fiscal capacity, allocating IDR 500 billion in emergency funds in the 2026 APBD, and integrating climate change mitigation into budget planning. These findings enrich the literature on fiscal federalism, provide a model for adaptive fiscal policy for Indonesia, and offer inspiration for other developing countries.